Compared the effect of anesthesia type in ceasarean birth on the primigravida Health (Journal of Hama University, 2021)
Birth is one of the most important moments of pregnant women, where The natural pregnancy lasts for 37-42 weeks at its end the fetus generates, There are two types of birth :natural and ceasarean birth, which Is similar to many surgery the requires anesthesia where there are two types :general and spinal anaethesia ,both of them have many side effects on the women. this study was conducted by 100 women to compare the impact of type anesthesia in ceasarean on primigravida Health in career and labor at the hospital tishreen university, have been selected by purposive sampling and data collected by using a questionnaire developed by the researcher.the results showed that the bleeding becomes less at primigravida after spinal anesthesia compared to the general anesthesia,as showed height of the nausea and vomiting and headache after the spinal anesthesia compared to the general anesthesia and the return of the movement bowl begins at primigravida after spinal anesthesia the earliest of general anesthesia and that urination of begins at primigravida after general anesthesia the earliest of spinal anesthesia. The study recommended conducting educational program by the nursing staff the aim of it explain positive and negative each of anesthesia type and side effect after cesarean on the mother and conducting a broader and more comprehensive study at the country level to compered the effect of type anesthesia in ceasarean birth on health of primigravida .